A Video-Based Introductory EEG Curriculum for Neurology Residents and Other EEG Learners - Jeremy J. Moeller; Pue Farooque; Gary Leydon; Moises Dominguez; Michael L. Schwartz; R. Mark Sadler (Association of American Medical Colleges, 2017)
Introduction It is difficult to provide standardized formal education in EEG because of time limitations and the availability of expert teachers. Video-based miniature lectures are a useful way to standardize the foundational principles of EEG and support learning during EEG/epilepsy rotations. Methods A curriculum of 10 EEG teaching videos was developed based on concepts outlined in the Accreditation Council for Graduate Medical Education Neurology Milestones. The videos were short (6-17 minutes) and made available to residents rotating through an EEG/epilepsy rotation in two neurology residency programs. Residents were instructed to review the videos and then apply their newly learned skills during EEG reading sessions. A survey about the process was completed at the end of the year. Results Twenty-one residents participated in the curriculum, and 15 (71%) responded to the survey. Two-thirds of respondents (10/15) said that they watched all of the videos, and 87% (13/15) watched at least half of the videos. All of the respondents used the videos as introductions to EEG concepts, and approximately half of respondents returned to the videos as a refresher after the rotation was over. Nearly all respondents either agreed or strongly agreed that the curriculum was a useful component of the rotation and helped them to understand difficult concepts. All strongly agreed that they would recommend the curriculum to other residents. Discussion A video-based approach to EEG teaching could complement existing curricula and ensure that learners have access to foundational miniature lectures when and where they need them.